Effect of Storage Time and Temperature of Equine Epididymis on the Viability, Motion Parameters, and Freezability of Epididymal Sperm - Monteiro, Gabriel Augusto [UNESP]; Guasti, Priscilla Nascimento [UNESP]; Rocha, Aline Silva [UNESP]; Martin, Ian [UNESP]; Sancler-Silva, Yamê Fabres Robaina [UNESP]; Freitas Dell'Aqua, Camila P. [UNESP]; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier, 2013)
The recovery of sperm from the epididymal cauda may be the last chance to obtain genetic material when sudden death or serious injuries occur in valuable stallions. However, the lack of technical knowledge regarding the storage and transportation of the epididymis often prevents the preservation of the sperm. Therefore, the aim of this study was to compare sperm parameters of sperm obtained immediately after orchiectomy with sperm recovered from epididymal cauda at different times after storage at 5°C and at room temperature (RT). For that, 48 stallions of different breeds were used. In group 1 (control group), eight stallions were used, and the harvest of the epididymal sperm was performed immediately after orchiectomy. In group 2, 40 stallions were used, which were divided into five groups according to the storage time of the epididymis after orchiectomy (6, 12, 18, 24, or 30 hours), making a total of eight stallions per group. One epididymis of each stallion was stored at 5°C, and the contralateral epididymis was stored at RT, both for the same period. The sperm parameters of total motility, progressive motility, progressive linear velocity, curvilinear velocity, percentage of rapid sperm, and plasma membrane integrity were evaluated in all the groups after sperm recovery, resuspension in a sperm freezing diluent, and thawing. In conclusion, the storage of the testis-epididymis complex at 5°C provided better preservation of epididymal sperm than the storage at RT, and regardless of the temperature, the progressive motility is the sperm parameter that is most sensitive to storage time. © 2013 Elsevier Inc.
Keywords: Cryopreservation; Epididymal spermatozoa; Sperm viability; Stallion; Storage; Equidae